Staying in Marriage is Not Enough: Influence of Marital Commitment and Adult Attachment Style on Marital Flourishing - Kusumawardhani, Sri Juwita; Mayangsari, Anggi; Rustyawati, Reny; Reswara, Ilham Phalosa (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
The aim of this research is to determine the influence of marital commitment and adult attachment style on the quality of marriage, specifically the marital flourishing of married young adults. In addition, the research participants were 263 respondents that were obtained using the Convenience Sampling technique, with the criteria young adult, (20-40 years old), married for at least 2 months, and living on Java Island. The instruments that were used were the Relationship Flourishing Scale (RFS), Marital Commitment Inventory (MCI), and Attachment Style Questionnaire (ASQ). The results showed that marital commitment (p = .000) and a secure attachment style (p = .000) significantly predict marital flourishing. Meanwhile, the fearful (p=.09), preoccupied (p=.78), and dismissing (p=.81) attachment styles do not influence marital flourishing. This study concludes that young adults who develop secure attachment patterns and a strong sense of marital commitment are more likely to experience high-quality marriages.